Designing Floor Tile Warehouse Layout Using Heuristic Approach Method to Increase Warehouse Capacity and Reduce Travel Distance - Sari, Tika Purnama; Ridwan, Ari Yanuar; Aurachman, Rio (International Journal of Innovation in Enterprise System, 2017)
XYZ Company is a distributor focused on distributing floor and wall ceramic tiles. XYZ Company has its own warehouse for storing finished goods with Last In First Out rotation. The XYZ Company Warehouse has an area of 12,312 m2 with floor stack system. An issue currently risen to the warehouse is that the warehouse is currently overcapacity that urges the company to store some of its SKUs to be stored out of the block or even outside the warehouse. The overcapacity causes some problems including accessibility problem, distribution of storage and retrieval activities, and damaged product. In addition, higher throughput items allocation were not placed near to the input/output point so the material handling went through long travel to do its activities and it caused higher total travel distance. This research is focused on determining the warehouse layout to increase warehouse storage capacity and reduce travel distance. The procedure taken to solve the issue is by redesigning warehouse layout through heuristic approach method. The heuristic approach method is comprised by algorithms that can determine dimensions of storage zone and material assignment needed in designing warehouse layout. It is aimed at having some combinations of lane depths and storage zones to increase the warehouse storage capacity by considering the throughput of each SKU. The next step is allocating the items so it can reduce the monthly travel distance. The proposed design layout, shows that warehouse capacity increases by 35.53% or 5,319 pallet positions and monthly travel distance decreases by 24.58% or 216,032 meters. Keywords—heuristic approach, travel distance, warehouse layout.